Pharmacological inhibition of fatty acid amide hydrolase attenuates social behavioural deficits in male rats prenatally exposed to valproic acid. (November 2016) - Kerr, Daniel M.; Gilmartin, Aoife; Roche, Michelle
Graphical abstract: Inhibition of FAAH, the enzyme that preferentially metabolises the endocannabinoid anandamide (AEA), using PF3845, attenuates social deficits in male rats prenatally exposed to valproic acid (VPA), an environmental animal model of autism. Abstract: Autism spectrum disorders are a group of neurodevelopmental disorders characterised by impaired social interaction, deficits in communication and repetitive stereotyped behaviours. The endocannabinoid system plays an important role in modulating emotionality and social responding, however there have been a paucity of studies investigating this system in autistic animal models. This study investigated the effect of inhibiting fatty acid amide hydrolyase (FAAH), the anandamide catabolic enzyme, on behavioural responding in the valproic acid (VPA) rat model of autism. Male rats prenatally exposed to VPA exhibit an autistic-like behavioural phenotype exemplified as thermal hypoalgesia, reduced social and exploratory behaviour, and enhanced repetitive behaviour. Systemic administration of the FAAH inhibitor PF3845 (10 mg/kg) attenuated the deficit in social behaviour observed in VPA exposed male animals without altering nociceptive, repetitive or exploratory behaviour. In comparison, female VPA exposed rats displayed enhanced repetitive and reduced exploratory behaviour, but no change in social behaviour or thermal nociceptive responding. PF3845 did not alter social, repetitive or thermal nociceptive responding, but reduced exploratory behaviour in a social context in VPA-, but not saline-, exposed females. These data indicate that FAAH inhibition elicits sexual dimorphic effects on behavioural responding in VPA exposed rodents, and support an important role for FAAH in the regulation of social behavioural deficits in autistic males.